The Effects of Holistic Caring Program on Self-care Behaviors and Self-esteem among Patients with Schizophrenia - Maha, Yupapun; Vatanasin, Duangjai; Nabkasorn, Chanudda (Journal of Phrapokklao Nursing College, Chanthaburi, 2019)
This quasi-experimental research aimed to examine the effects of holistic caring program on self-care behaviors and self-esteem among patients with schizophrenia. The samples included 24 patients with schizophrenia receiving services at Chao Phya Abhaibhubejhr Hospital, Prachinburi Province and were equally divided into an experimental group (n = 12) and a control group (n = 12). The research instruments comprised the holistic caring program, the Brief Psychiatric Rating Scale (BPRS), a questionnaire of demographic data, the self-care behaviors scale with the reliability of .81, and the self-esteem scale with the reliability of .83. The implementation and data collection were conducted from December, 2016 to March, 2017. Statistics used for data analysis included frequency, percentage, mean, standard deviation, independent t-test, and two-way repeated measures ANOVA with multiple comparisons by Bonferroni. The research results revealed that 1) at post-test and 1-month follow-up period, the experimental group had statistically significant higher mean scores of self-care behaviors and self-esteem than the control group (p < .001); and 2) at post-test and 1-month follow-up period, the experimental group had statistically significant higher mean scores of self-care behaviors and self-esteem than the pre-test period (p < .001). This research suggests that health care providers should apply this holistic caring program for promoting self-care behaviors and self-esteem of psychiatric patients and other patients with chronic disease.